Categorization and prediction of crimes of passion based on attitudes toward violence - Guan, Muzhen (International journal of offender therapy and comparative criminology, 2017)
The present study explored implicit and explicit attitudes toward violence in crimes of passion. Criminals (n = 96) who had perpetrated crimes of passion and students (n = 100) participated in this study. Explicit attitudes toward violence were evaluated using the Abnormal Personality Risk Inventory (APRI), and implicit attitude toward violence was evaluated using the Implicit Association Test (IAT). Results indicated that APRI scores of the perpetrators were significantly higher than that of the control group (p < .05), suggesting that explicit attitudes toward violence could discriminate between the criminals and the control group. There was a significant IAT effect demonstrating a negative implicit attitude toward violence in both the control group and in the criminals (n = 68); whereas there was a significant IAT effect manifesting a positive implicit attitude toward violence in the criminals (n = 16) only. These results suggest that combining explicit and implicit attitudes could provide an empirical classification of crimes of passion.